2021
DOI: 10.3390/agronomy11071421
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Grazing of Maize Residues Increased Carbon Sequestration in No-Tillage System: A Case of a Smallholder Farm in South Africa

Abstract: Despite the positive impact of no-tillage (NT) on soil organic carbon (SOC), its potential to reduce soil CO2 emission still needs enhancing for climate change mitigation. Combining NT with controlled-grazing of crop residues is known to increase nutrient cycling; however, the impacts on soil CO2 effluxes require further exploration. This study compared soil CO2 effluxes and SOC stocks from conventional tillage with free grazing (CTFG), NT with free grazing (NTFG), NT without grazing (NTNG), NT without crop re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The magnitude of soil respiration (0.14-20.55 g m À2 day À1 ) in the present study was comparable to that of a previous study conducted in the same field from June 2017 to December 2018 [0.17-17.99 g m À2 day À1 (Gong, Li, Lu, et al, 2021)]. The magnitude of the soil respiration in this study was slightly higher than that under different tillage and drainage treatments observed in the USA [2.38-9.57 g m À2 day À1 (Datta et al, 2013)], that under different tillage and grazing treatments observed in South Africa [0-15.50 g m À2 day À1 (Abdalla et al, 2021)], and that under different tillage treatments with crop residue retention observed in China [0.06-13.70 g m À2 day À1 (Wang et al, 2020)]. The difference in responses of soil respiration to NT and MP systems was site-specific.…”
Section: Effects Of the Microbiome On Soil Respirationmentioning
confidence: 49%
See 1 more Smart Citation
“…The magnitude of soil respiration (0.14-20.55 g m À2 day À1 ) in the present study was comparable to that of a previous study conducted in the same field from June 2017 to December 2018 [0.17-17.99 g m À2 day À1 (Gong, Li, Lu, et al, 2021)]. The magnitude of the soil respiration in this study was slightly higher than that under different tillage and drainage treatments observed in the USA [2.38-9.57 g m À2 day À1 (Datta et al, 2013)], that under different tillage and grazing treatments observed in South Africa [0-15.50 g m À2 day À1 (Abdalla et al, 2021)], and that under different tillage treatments with crop residue retention observed in China [0.06-13.70 g m À2 day À1 (Wang et al, 2020)]. The difference in responses of soil respiration to NT and MP systems was site-specific.…”
Section: Effects Of the Microbiome On Soil Respirationmentioning
confidence: 49%
“…The effects of NT on soil respiration are of some concern given the use of NT in soil conservation; however, the results have been inconsistent. Compared with conventional tillage (CT), NT has been shown to increase (Alskaf et al, 2021; Pareja‐Sánchez et al, 2019), reduce (Abdalla et al, 2021; Behnke et al, 2018) or not alter (Elder & Lal, 2008; Guardia et al, 2016) soil respiration. In contrast, little attention has been paid to the effects of winter cover crop rotation on soil respiration or their interaction with tillage regimes.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the negative correlations between soil CO 2 emissions and SOC and N content under degraded grassland (Table 3) point to the limited role of soil C and N content on soil C outputs from soils under degraded grassland conditions. As a final note, rotational grazing has great potential in increasing soil C stocks, reducing soil CO 2 emissions and enhancing land productivity (Abdalla, Mutema, et al, 2021; Chaplot et al, 2016). In addition to its high potential on rehabilitated degraded grass in a short time (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impacts of RG as an efficient practice to rehabilitate degraded grasslands on soil CO 2 emissions as the C outputs and the underlying factors need to be quantified. The current study hypothesized that high aboveground biomass production and SOCs induced by RG (Abdalla, Mutema, et al, 2021;Chaplot et al, 2016) would result in high gross soil CO 2 emissions (CO 2 -C per m 2 ), but low net soil CO 2 emissions (CO 2 -C per g C). As the net soil CO 2 emissions refer to the difference between the absorbed and released C, the low net CO 2 emissions imply an enhanced topsoil C stocks of the degraded grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation agriculture has been recommended by the FAO (2008) as a concept for resource-efficient crop production, but its benefits are controversial (Giller et al, 2011). Subsoil compaction in conservation agriculture has been noticed in several studies (Abdalla et al, 2021;Brouder and Gomez-Macpherson, 2014). Results presented in Chapter 4 of my thesis indicate also that practices related to conservation agriculture may lead to subsoil compaction and to a decline in wheat yields.…”
Section: Effectiveness Of Soil Compaction Management Measuresmentioning
confidence: 84%